Theimpact of civil gang injunctions on networked violence between the bloods and the crips - Bichler, Gisela (Crime & delinquency, 2019)
Comparing the centrality of gangs and changing structure in attack behavior, this study examines the effects of civil gang injunctions (CGIs) on violence involving 23 gangs (seven Bloods and 16 Crips) operating in Southern California. We mapped violence networks by linking defendants and victims named in 272 court cases prosecuted in the City of Los Angeles (1997-2015), involving at least one conviction for a violent crime and a defendant tried as an adult. The results show that a small number of gangs are centrally located in a dynamic web of non-reciprocated conflict that exhibited complex hierarchical structures. These results raise four implications for combating gang violence.